Altered calcitonin gene in a young patient with osteoporosis. Issue 6682 (6th May 1989) - Alevizaki, M.; Stevenson, J. C.; Girgis, S. I.; MacIntyre, I.; Legon, S.
Abstract : To assess whether calcitonin is important in maintaining the integrity of bone the calcitonin gene of a young male patient with osteoporosis and no detectable plasma concentrations of calcitonin was studied. Genomic Southern blots with various restriction enzymes showed no large abnormalities in his calcitonin gene. Genomic clones representing his calcitonin gene were then analysed. His gene encoded normal precursor polypeptides for calcitonin and calcitonin gene related peptide; the only abnormality identified was a single base insertion in the intron separating exons IV and V of the gene. The affected sequence is homologous with an intron sequence from beta globin that is implicated in splicing and forming a crucial intermediate structure during the maturation of messenger RNA. The change observed may be responsible for the patient's calcitonin deficiency and consequently for his condition, suggesting that calcitonin is important in preventing bone loss.